The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1055/s-0041-1726364
|View full text |Cite
|
Sign up to set email alerts
|

Approach to Common Sleep Disorders

Abstract: Sleep disorders are highly relevant in clinical practice given their prevalence as well as their impact on health outcomes and quality of life. The most common concerns are excessive daytime sleepiness, insomnia, disordered breathing, and abnormal movements or behaviors during sleep. A detailed but targeted history is vital, particularly from the sleep partner/witness. In-laboratory sleep testing (polysomnography and multiple sleep latency test) remains vital in the diagnosis of certain sleep disorders (such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 61 publications
(123 reference statements)
0
2
0
Order By: Relevance
“…Patients that met all of the following inclusion criteria were enrolled: (1)The diagnostic criteria of primary insomnia were referred to the American Academy of Sleep Medicine International Classification of Sleep Disorders [6] (3rd edition). ( 2) referred to the Diagnostic Efficacy Criteria of TCM Diseases and Syndromes [7] issued by the State Administration of Traditional Chinese Medicine.…”
Section: Inclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Patients that met all of the following inclusion criteria were enrolled: (1)The diagnostic criteria of primary insomnia were referred to the American Academy of Sleep Medicine International Classification of Sleep Disorders [6] (3rd edition). ( 2) referred to the Diagnostic Efficacy Criteria of TCM Diseases and Syndromes [7] issued by the State Administration of Traditional Chinese Medicine.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…Primary insomnia refers to insomnia caused by excluding drug abuse, mental disorders and other diseases. The clinical manifestations are difficulty in falling asleep, shallow sleep or short sleep frequency, early awakening etc., with the characteristics of recurrent and chronic persistence [1] . Some studies have found that [2,3] with the aggravation of insomnia, patients with insomnia may have a decline in cognitive function such as attention, memory and comprehension, and even increase the risk of dementia or depression.…”
Section: Introductionmentioning
confidence: 99%